Hadron structure from inclusive and exclusive cross-sections in ep scattering - Cooper-Sarkar, Amanda (Array, 2008)
The contribution of both inclusive and exclusive cross-section data from HERA to our knowledge of parton distribution functions is reviewed and future prospects are outlined.